The impact of real exchange rate volatility on the export of Turkish electrical appliances - Cetin, Rahmi; Karakaya, Etem (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper examines the impact of real exchange rate volatility on the demand for electrical exports, which is the second largest sub-sector of machinery in Turkey, by employing multivariate cointegration and error correction methods. The model was estimated for two-digit electrical exports (SITC 77), using quarterly data for the period 1995-2010. Our estimation results suggest that real exchange rate exerts a negative and significant impact on electrical exports both in the long and short term, while its volatility has only a positive and significant impact in the long run. In addition, the results of the long-term export model indicate that foreign income also has a positive and significant impact on Turkish electrical exports
Argumenta Oeconomica, 2013, Nr 1 (30), s. 109-126
Keywords: real exchange rate volatility; electrical exports; cointegration; Turkey